PENERAPAN KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Hasan, Hasbi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
One of the most significant changes contained in the UU No. 11 Tahun 2012 One of the most significant changes contained in the UU No. 11 Tahun 2012 is to accomodate principles of restorative justice and the principle of diversion in the juvenile justice system . Nevertheless, the application of the principles of restorative justice in the juvenile justice system are set out in the UU No. 11 Tahun 2012, tend to be partial and non-exhaustive . This is caused by the presence of common misconceptions in the understanding of restorative justice as an attempt to seek a peaceful settlement of the conflict out of court . This study shows that restorative justice is essentially complement rather than replace the criminal justice system . Therefore , restorative justice programs can be integrated into the whole process of juvenile justice without compromising the basic principles and main objectives of restorative justice , and at the same time , did not downplay the role of juvenile justice system that is based on formal legal requirements. Keywords: restorative justice, juvenile justice, crime, diversion.